The Interest Considered In The Holy Quran (Journal of the College of Basic Education, 2026)
Islamic Sharia was originally revealed to achieve the welfare of people and to avert harm from them. This is the essence of the mercy embodied in it and in its Messenger, peace be upon him. Our research aims to present examples of the benefits brought by Sharia, which vary according to different considerations. These masalih are regarded as legitimate legal proofs. The study also outlines the conditions for these masalih and how they are to be applied, as well as presenting what the Qur’an has established in terms of such benefits, being the primary source of legislation in Islam, along with its stories that took these interests into account.